The inconsistency of religious practice among converts and tolerance education strategies: Efforts to achieve family harmony - Nurkhayati; M. Jamal; Muhammad Syakur; Sumarjoko; Husna Nashihin; Rohmat (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This study aims to analyze the inconsistency of religious practice among converts (muallaf) and explore tolerance education strategies as efforts to achieve family harmony. Religious conversion often brings significant psychological, social, and familial adjustments, particularly in pluralistic societies. In many cases, converts experience fluctuating religious commitment due to identity reconstruction, social pressure, and limited support systems. These inconsistencies may trigger tension within families, especially in interfaith or culturally diverse contexts. This research employs a qualitative approach using a case study design involving converts and their families in Indonesia. Data were collected through in-depth interviews, participant observation, and document analysis. The findings reveal that religious inconsistency is influenced by emotional instability, limited religious literacy, social stigma, and inadequate family communication. The study further identifies that tolerance based education strategies such as dialogical communication, inclusive religious understanding, and family-based value reinforcement significantly contribute to strengthening emotional bonds and maintaining family harmony. This research recommends integrating structured tolerance education programs within family and community religious guidance frameworks.